How Do Soccer Players Adjust Their Activity in Team Coordination? An Enactive Phenomenological Analysis - Gesbert, Vincent; Durny, Annick; Hauw, Denis (Frontiers in Psychology, 2017)
This study examined how individual team members adjust their activity to the needs for collective behavior. To do so, we used an enactive phenomenological approach and explored how soccer players’ lived experiences were linked to the active regulation of team coordination during eight offensive transition situations. These situations were defined by the shift from defensive to offensive play following a change in ball possession. We collected phenomenological data, which were processed in four steps. First, we reconstructed the diachronic and synchronic dynamics of the players’ lived experiences across these situations in order to identify the units of their activity. Second, we connected each player’s units of activity side-by-side in chronological order in order to identify the collective units. Each connection was viewed as a collective regulation mode corresponding to which and how individual units were linked at a given moment. Third, we clustered each collective unit using the related objectives within three modes of regulation ‒ local (L), global (G), and mixed (M). Fourth, we compared the occurrences of these modes in relation to the observable key moments in the situations in order to identify typical patterns. The results indicated four patterns of collective regulation modes. Two distinct patterns were identified without ball possession: reorganize the play formation (G and M) and adapt to the actions of putting pressure on the ball carrier (M). Once the ball was recovered, two additional patterns emerged: be available to get the ball out of the recovery zone (L) and shoot for the goal (L and M). These results suggest that team coordination is a fluctuating phenomenon that can be described through the more or less predictable chaining between these patterns. They also highlight that team coordination is supported by several modes of regulation, including our proposal of a new mode of interpersonal regulation. We conclude that future research should investigate the effect of training on the enaction of this mode in competition.